Facile hydrothermal synthesis of layered 1T′ MoTe2 nanotubes as robust hydrogen evolution electrocatalysts - Lei, Yuxi; Xiao, Xuefeng; Ma, Tianpeng; Li, Weiyin; Zhang, Huan; Ma, Chao (Frontiers in Chemistry, 2022)
Layered transition metal dichalcogenides (TMDs), such as molybdenum ditelluride (MoTe2), have attracted much attention because of their novel structure-related physicochemical properties. In particular, semi-metallic-phase MoTe2 (1T') is considered as a competitive candidate for low-cost electrocatalysts for water splitting. However, there are few reports on the simple hydrothermal synthesis of MoTe2 nanostructures compared with other layered TMDs. In this study, a facile one-step hydrothermal process was developed for the fabrication of layered MoTe2, in which uniform nanotubes with a few layers of 1T' MoTe2 were fabricated at a lower temperature for the first time. The as-obtained MoTe2 nanotubes were fully characterized using different techniques, which revealed their structure and indicated the presence of layered 1T' nanocrystals. The efficient activity of MoTe2 nanotubes for the electrocatalytic hydrogen evolution reaction (HER) in 0.5 M H2SO4 was demonstrated by the small Tafel slope of 54 mV/dec and endurable ability, which is attributed to the abundant active sites and remarkable conductivity of 1T' MoTe2 with a few-layer feature. This provides a facile method for the design and construction of efficient layered MoTe2 based electrocatalysts.